2021
DOI: 10.1002/hep.31568
|View full text |Cite
|
Sign up to set email alerts
|

Activating Adenosine Monophosphate–Activated Protein Kinase Mediates Fibroblast Growth Factor 1 Protection From Nonalcoholic Fatty Liver Disease in Mice

Abstract: Background and Aims Fibroblast growth factor (FGF) 1 demonstrated protection against nonalcoholic fatty liver disease (NAFLD) in type 2 diabetic and obese mice by an uncertain mechanism. This study investigated the therapeutic activity and mechanism of a nonmitogenic FGF1 variant carrying 3 substitutions of heparin‐binding sites (FGF1△HBS) against NAFLD. Approach and Results FGF1△HBS administration was effective in 9‐month‐old diabetic mice carrying a homozygous mutation in the leptin receptor gene (db/db) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 35 publications
(65 reference statements)
2
54
0
1
Order By: Relevance
“…It has also been reported that adiponectin improves the function of endothelial cells by activating the AMPK pathway (Chen et al, 2009). Moreover, the activation of AMPK was shown to mediate the protection of fibroblast growth factor 1 from non-alcoholic fatty liver disease in mice by improving lipid metabolism (Lin et al, 2020). These findings suggested that AMPK may be involved in the protective effect of nmFGF1 on stroke in type 2 diabetic (T2D) mice and acts by regulating glucolipid metabolism and angiogenesis.…”
Section: Introductionmentioning
confidence: 87%
“…It has also been reported that adiponectin improves the function of endothelial cells by activating the AMPK pathway (Chen et al, 2009). Moreover, the activation of AMPK was shown to mediate the protection of fibroblast growth factor 1 from non-alcoholic fatty liver disease in mice by improving lipid metabolism (Lin et al, 2020). These findings suggested that AMPK may be involved in the protective effect of nmFGF1 on stroke in type 2 diabetic (T2D) mice and acts by regulating glucolipid metabolism and angiogenesis.…”
Section: Introductionmentioning
confidence: 87%
“…AMPK, as a pivotal player in maintaining cellular energy homeostasis, is reported to regulate multiple metabolic processes. Previous articles indicated that the loss of AMPK activation significantly aggravated liver inflammation and lipid disorders in mouse fibrotic models ( Lin et al, 2020 ; Zhao et al, 2020 ). In addition, the protective functions of AMPK phosphorylation are also highlighted recently, including preventing oxidative stress and attenuating alcoholic liver disease progression ( Lu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Qian Lin et al constructed liver-specific AMPK knockout mice and investigated the specific role of phosphorylated AMPK in fibrotic steatohepatitis. The hepatic depletion of AMPK completely disrupted hepatic lipid metabolism, triggered inflammatory response and aggregated liver fibrosis in a western diet-induced liver steatotic mouse model ( Lin et al, 2020 ). Collectively, considering the vital role that AMPK plays in the progression of fibrotic liver injury, the identification of novel drugs targeting AMPK is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, AMPK, a diffusely known energy sensor, has been reported to play a crucial role in antioxidant responses ( Wu et al, 2018 ; Lin et al, 2020 ). We measured AMPK activity by detecting phosphorylation of AMPKα subunit at threonine 172.…”
Section: Discussionmentioning
confidence: 99%